High-performance low-cost PVC (polyvinyl chloride) composite material and application thereof in cable protection pipe

By adopting high-performance and low-cost PVC composite materials, the problems of high cost, insufficient impact resistance and wear resistance of cable protection tubes are solved, cost reduction and performance improvement are achieved, and the service life of cable protection tubes is extended.

CN119752068AInactive Publication Date: 2025-04-04WUXI HAILITE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411986468.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cable protection tubes have high cost and need to be improved impact resistance and wear resistance, which limits its scope of application and service life.

Method used

A high-performance low-cost PVC composite material is used, and the preparation method includes stirring and mixing PVC, modified filler, PNBR, impact agent, heat stabilizer and lubricant, heating, stirring, melting, extruding, and granulating, and the obtained composite material is used to prepare cable protection tubes.

Benefits of technology

It has achieved the reduction of the production cost of cable protection pipes, improved their impact resistance, wear resistance and thermal stability, and extended their service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752068A_ABST
    Figure CN119752068A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance low-cost PVC composite material and application thereof in a cable protection tube, and belongs to the technical field of cable materials.The preparation method of the high-performance low-cost PVC cable protection tube comprises the steps that PVC, modified filler, PNBR, an impact modifier, a heat stabilizer and a lubricant are stirred and mixed to be uniform, heated and stirred, and the high-performance low-cost PVC composite material is obtained; wherein aldehyde modified nano calcium carbonate-modified fly ash and 3-chloroperoxybenzoic acid are added into dichloromethane, a reaction is carried out under the low-temperature condition, after the reaction is finished, filtering, washing and drying are carried out, and modified filler is obtained; the PVC cable protection pipe prepared by the invention not only has the characteristics of low cost and excellent impact resistance, but also has good wear resistance and degradation resistance, and is suitable for working in an underground environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable materials, and in particular to a high-performance and low-cost PVC composite material and its application in a cable protection tube. Background Art

[0002] Cable protection tube, also called cable sheath or cable sheath tube, is laid on the outer layer of the cable, mainly to protect the cable. It is usually made of corrosion-resistant, wear-resistant, pressure-resistant and other materials, which can effectively extend the service life of the cable and ensure the safe operation of the cable. Cable protection tubes are divided into PVC tubes, CPVC tubes, fiberglass tubes, hot-dip plastic tubes and cement vinylon tubes. Among them, CPVC cable protection tube is a new type of buried high-voltage power cable protection tube made of PVC resin as masterbatch, adding anti-impact agent, stabilizer and other auxiliary materials through high-speed extrusion. It has the advantages of high strength, good flexibility, high temperature resistance and corrosion resistance, but its preparation cost and processing difficulty are significantly higher than PVC tubes, which limits its scope of application. Polyvinyl chloride cable protection tube is a plastic pipe made of polyvinyl chloride resin and various functional additives after mixing or granulation and extruding with an extruder, and the amount used accounts for more than half of the amount of cable protection tube; as an important carrier for cable laying, the amount of underground cable protection tube is increasing, and the quality of cable protection tube has also attracted attention. The current disadvantages of PVC materials include poor thermal stability and poor toughness. Although PVC has good chemical resistance, long-term exposure to chemical media may cause degradation, which is not conducive to the life of the PVC cable protection tube.

[0003] Chinese patent CN112300515A discloses a heat-resistant polyvinyl chloride cable protection tube and a preparation method thereof, wherein the cable protection tube is prepared by mixing PVC resin, styrene-maleic anhydride block copolymer, glass fiber, filler, composite stabilizer, chlorinated polyethylene, lubricant and colorant in a mass ratio of 100:(20-30):(25-30):(20-25):(3-3.5):(5-6):(1.2-1.5):(0.3-0.8). The polyvinyl chloride cable protection tube prepared by the invention has good heat resistance and bending strength, but its wear resistance needs to be strengthened. Chinese patent CN118165434B discloses a high-strength PVC and a preparation method, and a cable protection tube, wherein the high-strength PVC is prepared from PVC, silicone rubber, a compatibilizer, an ACR resin, chlorinated polyethylene, a filler, a heat stabilizer, polyethylene wax and stearic acid in a mass ratio of (60-80):(15-20):(4-6):(2.5-3.5):(5-7):(10-15):(3-5):(0.8-1.5):(1-2). The impact resistance of the high-strength PVC cable protection tube prepared by this invention needs to be further improved, and the production process provided by this invention has high requirements and high production costs, which is not conducive to large-scale use.

[0004] In summary, developing a high-performance, low-cost PVC composite material has broad market value and important practical significance, especially in its application in cable protection tubes. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-performance and low-cost PVC composite material and its application in cable protection tubes, which solves the problems in the prior art that the cable protection tubes are high in cost and the anti-red model needs to be further improved, extends the service life, and has practical significance and value.

[0006] In order to achieve the above object, the present invention provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0007] PVC, modified filler, PNBR, impact resistant agent, heat stabilizer and lubricant are mixed evenly, heated, stirred, melted, extruded and granulated to obtain high-performance and low-cost PVC composite material;

[0008] The preparation method of the modified filler comprises the following steps:

[0009] Adding aldehyde-modified nano calcium carbonate-modified fly ash and 3-chloroperoxybenzoic acid into dichloromethane, reacting under low temperature conditions, filtering, washing and drying after the reaction is completed, and obtaining a modified filler;

[0010] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0011] Step (1) in a nitrogen atmosphere, adding olefin-modified nano-calcium carbonate and 9-decenal to N,N-dimethylformamide, stirring, adding ammonium persulfate, heating, reacting, filtering, washing, and drying to obtain aldehyde-modified nano-calcium carbonate;

[0012] Step (2) under an inert gas atmosphere, adding hydroxylated fly ash and 4-amino-3-fluoroallyl benzoate to N,N-dimethylformamide, adding potassium carbonate and mixing evenly, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain modified fly ash;

[0013] Step (3) dispersing the aldehyde-modified nano-calcium carbonate into anhydrous ethanol, adding potassium hydroxide and modified fly ash after uniform dispersion, heating, reacting, filtering, washing, and drying to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0014] Preferably, the mass ratio of PVC, modified filler, PNBR, impact resister, heat stabilizer and lubricant is (80-100):(12-18):(5-9):(8-16):(2-4):(1.4-1.8).

[0015] Preferably, the mass ratio of aldehyde-modified nano-calcium carbonate-modified fly ash, 3-chloroperbenzoic acid and dichloromethane is (100-140):(400-600):(2000-4000); the reaction temperature is 1-5°C, and the reaction time is 2-4h.

[0016] Preferably, the mass ratio of olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate is (60-80):(2000-4000):(30-50):(1.8-3); the reaction temperature is 65-75°C, and the reaction time is 2.5-4.5h.

[0017] Preferably, the mass ratio of hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate is (70-90):(10-14):(800-1000):(2-4); the reaction temperature is 45-65°C, and the reaction time is 35-43h.

[0018] Preferably, the mass ratio of aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash is (60-80):(1500-4500):(3-7):(20-28); the reaction temperature is 60-80°C, and the reaction time is 3-5h.

[0019] Preferably, the heat stabilizer is a calcium-zinc composite stabilizer.

[0020] Preferably, the impact-resistant agent is any one of silicone rubber and CPE.

[0021] Preferably, the lubricant is any one of paraffin and stearic acid.

[0022] Preferably, the preparation method of olefin-modified nano calcium carbonate is as follows:

[0023] The nano-calcium carbonate, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane are uniformly mixed, heated to react, centrifuged and dried after the reaction is completed to obtain olefin-modified nano-calcium carbonate;

[0024] Wherein, the mass ratio of nano calcium carbonate, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane is (70-90):(2000-4000):(30-35);

[0025] The reaction temperature is 60-80°C and the reaction time is 7-9h.

[0026] Preferably, the preparation method of hydroxylated fly ash is as follows:

[0027] Add fly ash into sodium hydroxide aqueous solution, stir evenly, react for 4 hours at 100-120°C under condensation reflux conditions, then cool to room temperature, filter, wash and dry to obtain hydroxylated fly ash;

[0028] The drying conditions are as follows: drying at 180-190°C for 10-12h;

[0029] The mass ratio of fly ash to sodium hydroxide aqueous solution is 1:300-400; the concentration of sodium hydroxide aqueous solution is 2-4 mol / L.

[0030] Preferably, the high-performance and low-cost PVC composite material is prepared by the method for preparing the high-performance and low-cost PVC composite material.

[0031] Preferably, the high-performance and low-cost PVC composite material is used in cable protection tubes.

[0032] Preferably, the application of the high-performance and low-cost PVC composite material to prepare a cable protection tube comprises the following steps:

[0033] S1: Put PVC, modified filler, PNBR, impact agent, heat stabilizer and lubricant into a high-speed mixer, and mix them at high speed and low speed in sequence to obtain a mixture;

[0034] S2: The mixed material is extruded through a twin-screw extruder, cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0035] Preferably, the high-speed mixing condition is: stirring at a rotation speed of 900-1100 r / min for 12-16 min.

[0036] Preferably, the low-speed mixing condition is: stirring at a rotation speed of 70-110 r / min for 7-9 min.

[0037] Preferably, in the twin-screw extruder, the die temperature is 170-200°C.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. In the present invention, fly ash is used as a fine particle filler to improve the fluidity of PVC, so that PVC can flow better and fill the mold during processing, especially showing good fluidity during processing such as extrusion and injection molding. It can also reduce the viscosity of PVC and reduce the friction resistance during processing, thereby improving production efficiency; at the same time, it also has good rigidity and high hardness. After these particles are dispersed in the PVC matrix, they can effectively resist the action of external forces and reduce the deformation of the material. Since the particle size of fly ash is usually small, its addition can make the material more compact, thereby improving the overall rigidity and hardness of the material. The modified fly ash can further improve the dispersibility and compatibility. The hydroxyl group in the hydroxylated fly ash reacts with the chlorine group in 4-amino-3-fluoroallyl benzoate to obtain an ether bond, which increases its chemical resistance, and the modified fly ash has a toughening effect.

[0040] 2. In the present invention, the introduced nano calcium carbonate is an inorganic heat-resistant particle, and its thermal decomposition temperature is higher than 500°C. The nano calcium carbonate particles with better dispersibility and compatibility are added to the PVC matrix, wrapping the polymer in the matrix, blocking the heat from entering the matrix, inhibiting the decomposition of PVC, thereby increasing the initial thermal decomposition temperature of PVC, improving the thermal stability to a certain extent, and extending the service life; it can also improve the toughness and bending strength of plastics, reduce the plasticizing temperature, and facilitate processing. The dispersibility of olefin-modified nano calcium carbonate is better than that of nano calcium carbonate. The olefin-modified nano calcium carbonate reacts with the unsaturated bond in 9-decenal under the action of the initiator ammonium persulfate, and the two are stably connected to obtain aldehyde-modified nano calcium carbonate, wherein the presence of the alkyl chain gives it a certain flexibility, and at low temperatures, the long-chain alkyl structure helps to improve the low temperature resistance of the material. The aldehyde group in the aldehyde-modified nano-calcium carbonate reacts with the amino group in the modified fly ash to generate a carbon-nitrogen double bond, which has a larger chemical bond energy and improves thermal stability; at the same time, the aldehyde-modified nano-calcium carbonate can form better compatibility with the polymer, and its surface functional group can interact more strongly with the PVC molecular chain, enhancing its filling effect and interfacial adhesion. The aldehyde-modified nano-calcium carbonate-modified fly ash prepared in this way contains unsaturated bonds, and under the action of 3-chloroperbenzoic acid, the double bonds are epoxidized to obtain a modified filler; the epoxy group contained in the modified filler can absorb HCl released by the degradation of the PVC material, weakening its catalytic effect on degradation, which is beneficial to prolonging the life of the PVC matrix material.

[0041] 3. In the present invention, the introduced chlorinated polyethylene (CPE) is added to the PVC material, which can not only reduce the processing temperature of PVC and improve the processing performance, but also improve the impact resistance of the PVC material, improve its toughness and strength, make the cable protection tube not easy to break, and improve its durability. The heat stabilizer plays a stabilizing role to prevent the PVC from thermal decomposition during processing. Stearic acid promotes processing performance, adjusts hardness and lubricates. The PNBR rubber particles have good compatibility with the PVC substrate, and they are in a mesh shape in the PVC substrate to increase toughness and low temperature resistance. Fly ash, as a waste resource, has a low cost, and its addition to the low-cost PVC material can effectively reduce the material cost of plastics, the production process is simple, the raw material cost is low, the processing difficulty is reduced, and it is suitable for a wide range of ordinary underground environment applications, suitable for large-scale production, and has certain economic applicability. The cable protection tube prepared by the present invention has good wear resistance, degradation resistance, thermal stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The figure is a process flow chart for preparing the high-performance and low-cost PVC composite material of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides a method for preparing olefin-modified nano calcium carbonate, comprising the following steps:

[0046] Nano calcium carbonate, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane were mixed evenly in a mass ratio of 70:2000:30, reacted at 60° C. for 9 hours, and after the reaction was completed, centrifuged and dried to obtain olefin-modified nano calcium carbonate.

[0047] Example 2

[0048] This embodiment provides a method for preparing hydroxylated fly ash, comprising the following steps:

[0049] The fly ash and 2 mol / L sodium hydroxide aqueous solution were mixed at a powder mass ratio of 1:300, stirred at 140 r / min for 4 min, reacted at 120°C under condensation reflux conditions for 4 h, then cooled to room temperature, filtered, washed with deionized water, and dried at 190°C for 10 h to obtain hydroxylated fly ash.

[0050] Example 3

[0051] This embodiment provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0052] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 80:12:5:8:2:1.4, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a high-performance and low-cost PVC composite material;

[0053] Obtain high-performance and low-cost PVC composite materials;

[0054] The preparation method of the modified filler comprises the following steps:

[0055] The aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperoxybenzoic acid and dichloromethane were mixed in a mass ratio of 100:400:2000, reacted at 1°C for 4 hours, filtered, washed with deionized water, and dried at 80°C for 10 hours to obtain a modified filler;

[0056] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0057] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 60:2000:30:1.8, reacted at 65° C. for 4.5 h, filtered, washed with acetone 3 times, and dried at 70° C. for 12 h to obtain aldehyde-modified nano-calcium carbonate;

[0058] Step (2) In an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 70:10:800:2, reacted at 45°C for 43 hours, filtered, washed with anhydrous ethanol for 3 times, and dried at 100°C for 9 hours to obtain modified fly ash;

[0059] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 60:1500:3:20, react at 60°C for 5 hours, filter, wash with deionized water, and dry at 70°C for 7 hours to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0060] Example 4

[0061] This embodiment provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0062] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 85:13.5:6:10:2.5:1.5, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a high-performance and low-cost PVC composite material;

[0063] The preparation method of the modified filler comprises the following steps:

[0064] Aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperoxybenzoic acid and dichloromethane were mixed in a mass ratio of 110:450:2500, reacted at 2°C for 3.5h, filtered, washed with deionized water, and dried at 85°C for 9.5h to obtain a modified filler;

[0065] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0066] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 65:2500:35:2.1, reacted at 67° C. for 4 h, filtered, washed with acetone 3 times, and dried at 75° C. for 11.5 h to obtain aldehyde-modified nano-calcium carbonate;

[0067] Step (2) In an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 75:11:850:2.5, reacted at 50° C. for 41 hours, filtered, washed with anhydrous ethanol 3 times, and dried at 102° C. for 8.5 hours to obtain modified fly ash;

[0068] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 65:2250:4:22, react at 65°C for 4.5 hours, filter, wash with deionized water, and dry at 75°C for 6.5 hours to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0069] Example 5

[0070] This embodiment provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0071] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 90:15:7:12:3:1.6, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a high-performance and low-cost PVC composite material;

[0072] The preparation method of the modified filler comprises the following steps:

[0073] Aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperbenzoic acid and dichloromethane were mixed in a mass ratio of 120:500:3000, reacted at 3°C ​​for 3h, filtered, washed with deionized water, and dried at 90°C for 9h to obtain a modified filler;

[0074] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0075] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 70:3000:40:2.4, reacted at 70° C. for 3.5 hours, filtered, washed with acetone for 3 times, and dried at 80° C. for 11 hours to obtain aldehyde-modified nano-calcium carbonate;

[0076] Step (2) in an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 80:12:900:3, reacted at 55° C. for 39 hours, filtered, washed with anhydrous ethanol three times, and dried at 105° C. for 8 hours to obtain modified fly ash;

[0077] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 70:3000:5:24, react at 70°C for 4 hours, filter after the reaction, wash with deionized water, and dry at 80°C for 6 hours to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0078] Example 6

[0079] This embodiment provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0080] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 95:16.5:8:14:3.5:1.7, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a high-performance and low-cost PVC composite material;

[0081] The preparation method of the modified filler comprises the following steps:

[0082] Aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperoxybenzoic acid and dichloromethane were mixed in a mass ratio of 130:550:3500, reacted at 4°C for 2.5 hours, filtered, washed with deionized water, and dried at 95°C for 8.5 hours to obtain a modified filler;

[0083] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0084] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 75:3500:45:2.7, reacted at 72° C. for 3 h, filtered, washed with acetone 3 times, and dried at 85° C. for 10.5 h to obtain aldehyde-modified nano-calcium carbonate;

[0085] Step (2) in an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 85:13:950:3.5, reacted at 60° C. for 37 h, filtered, washed with anhydrous ethanol 3 times, and dried at 108° C. for 7.5 h to obtain modified fly ash;

[0086] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 75:3750:6:26, react at 75°C for 3.5 hours, filter, wash with deionized water, and dry at 85°C for 5.5 hours to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0087] Example 7

[0088] This embodiment provides a method for preparing a high-performance and low-cost PVC composite material, comprising the following steps:

[0089] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 100:18:9:16:4:1.8, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a high-performance and low-cost PVC composite material;

[0090] The preparation method of the modified filler comprises the following steps:

[0091] The aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperoxybenzoic acid and dichloromethane were mixed in a mass ratio of 140:600:4000, reacted at 5°C for 2h, filtered, washed with deionized water, and dried at 100°C for 8h to obtain a modified filler;

[0092] The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps:

[0093] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 80:4000:50:3, reacted at 75° C. for 2.5 h, filtered, washed with acetone 3 times, and dried at 90° C. for 10 h to obtain aldehyde-modified nano-calcium carbonate;

[0094] Step (2) in an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 90:14:1000:4, reacted at 65°C for 35h, filtered, washed with anhydrous ethanol 3 times, and dried at 110°C for 7h to obtain modified fly ash;

[0095] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 80:4500:7:28, react at 80°C for 3 hours, filter, wash with deionized water, and dry at 90°C for 5 hours to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

[0096] Example 8

[0097] This embodiment provides a method for preparing a high-performance and low-cost PVC cable protection tube, comprising the following steps:

[0098] S1: The high-performance and low-cost PVC composite material prepared in Example 3 was placed in a high-speed mixer, discharged at 130° C., and stirred at a speed of 900 r / min for 16 min; discharged at 50° C., and stirred at a speed of 70 r / min for 9 min to obtain a mixture;

[0099] S2: The mixed material is extruded through a twin-screw extruder with a die head temperature of 170°C, and the outer wall and the inner wall are formed at one time, and then cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0100] Example 9

[0101] This embodiment provides a method for preparing a high-performance and low-cost PVC cable protection tube, comprising the following steps:

[0102] S1: Put the high-performance and low-cost PVC composite material prepared in Example 4 into a high-speed mixer, discharge the material at a temperature of 130° C., and stir at a speed of 950 r / min for 15 min; discharge the material at a temperature of 50° C., and stir at a speed of 80 r / min for 8.5 min to obtain a mixture;

[0103] S2: The mixed material is extruded through a twin-screw extruder with a die head temperature of 177°C, and the outer wall and the inner wall are formed at one time, and then cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0104] Example 10

[0105] This embodiment provides a method for preparing a high-performance and low-cost PVC cable protection tube, comprising the following steps:

[0106] S1: Put the high-performance and low-cost PVC composite material prepared in Example 3 into a high-speed mixer, discharge the material at a temperature of 130° C., and stir at a speed of 1000 r / min for 14 min; discharge the material at a temperature of 50° C., and stir at a speed of 90 r / min for 8 min to obtain a mixture;

[0107] S2: The mixed material is extruded through a twin-screw extruder with a die head temperature of 185°C, and the outer wall and the inner wall are formed at one time, and then cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0108] Embodiment 11

[0109] This embodiment provides a method for preparing a high-performance and low-cost PVC cable protection tube, comprising the following steps:

[0110] S1: Put the high-performance and low-cost PVC composite material prepared in Example 3 into a high-speed mixer, discharge the material at a temperature of 130° C., and stir at a speed of 1050 r / min for 13 min; discharge the material at a temperature of 50° C., and stir at a speed of 100 r / min for 7.5 min to obtain a mixture;

[0111] S2: The mixed material is extruded through a twin-screw extruder with a die head temperature of 192°C, and the outer wall and the inner wall are formed at one time, and then cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0112] Example 12

[0113] This embodiment provides a method for preparing a high-performance and low-cost PVC cable protection tube, comprising the following steps:

[0114] S1: Put the high-performance and low-cost PVC composite material prepared in Example 3 into a high-speed mixer, discharge the material at a temperature of 130° C., and stir at a speed of 1100 r / min for 12 min; discharge the material at a temperature of 50° C., and stir at a speed of 110 r / min for 7 min to obtain a mixture;

[0115] S2: The mixed material is extruded through a twin-screw extruder with a die head temperature of 200°C, the outer wall and the inner wall are formed at one time, and then cooled, shaped, cut, and expanded to obtain a cable protection tube.

[0116] Comparative Example 1

[0117] This comparative example provides a method for preparing a PVC composite cable protection tube, comprising the following steps:

[0118] S1: Put the PVC composite material into a high-speed mixer, discharge the material at 130°C, and stir at a speed of 900r / min for 16min; discharge the material at 50°C, and stir at a speed of 70r / min for 9min to obtain a mixed material;

[0119] S2: Extruding the mixed material through a twin-screw extruder with a die head temperature of 170°C, forming the outer wall and the inner wall at one time, cooling, shaping, cutting, and expanding to obtain a cable protection tube;

[0120] The preparation method of the PVC composite material comprises the following steps:

[0121] PVC, modified filler, PNBR, CPE, calcium zinc composite stabilizer and stearic acid were mixed in a mass ratio of 80:12:5:8:2:1.4, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a PVC composite material;

[0122] The preparation method of the modified filler comprises the following steps:

[0123] Step (1) In a nitrogen atmosphere, olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate are stirred and mixed in a mass ratio of 60:2000:30:1.8, reacted at 65° C. for 4.5 h, filtered, washed with acetone 3 times, and dried at 70° C. for 12 h to obtain aldehyde-modified nano-calcium carbonate;

[0124] Step (2) In an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 70:10:800:2, reacted at 45°C for 43 hours, filtered, washed with anhydrous ethanol for 3 times, and dried at 100°C for 9 hours to obtain modified fly ash;

[0125] Step (3) Mix aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash in a mass ratio of 60:1500:3:20, react at 60°C for 5 hours, filter, wash with deionized water, and dry at 70°C for 7 hours to obtain a modified filler.

[0126] Comparative Example 2

[0127] This comparative example provides a method for preparing a PVC composite cable protection tube, comprising the following steps:

[0128] S1: Put the PVC composite material into a high-speed mixer, discharge the material at 130°C, and stir at a speed of 900r / min for 16min; discharge the material at 50°C, and stir at a speed of 70r / min for 9min to obtain a mixed material;

[0129] S2: Extruding the mixed material through a twin-screw extruder with a die head temperature of 170°C, forming the outer wall and the inner wall at one time, cooling, shaping, cutting, and expanding to obtain a cable protection tube;

[0130] The preparation method of the PVC composite material comprises the following steps:

[0131] PVC, olefin-modified nano calcium carbonate, modified fly ash, PNBR, CPE, calcium-zinc composite stabilizer and stearic acid were mixed in a mass ratio of 80:9:3:5:8:2:1.4, stirred at a speed of 200 r / min for 15 min, melted, extruded and granulated to obtain a PVC composite material;

[0132] The preparation method of modified fly ash comprises the following steps:

[0133] In an Ar atmosphere, hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate were mixed in a mass ratio of 70:10:800:2, reacted at 45°C for 43 hours, and after the reaction was completed, filtered, washed with anhydrous ethanol for 3 times, and dried at 100°C for 9 hours to obtain modified fly ash.

[0134] In the present invention, the olefin-modified nano-calcium carbonate in Examples 3-7 and Comparative Examples 1-2 are all prepared using the olefin-modified nano-calcium carbonate prepared in Example 1.

[0135] In the present invention, the hydroxylated fly ash in Examples 3-7 and Comparative Examples 1-2 all adopts the hydroxylated fly ash prepared in Example 2.

[0136] In the present invention, PVC comes from Yuyao Qihong Plastic Chemical Co., Ltd.; PNBR comes from Beijing Chemical Research Institute of China Petrochemical Corporation, VP-401, which is an ultrafine nitrile rubber powder; nano calcium carbonate comes from Anhui Xueling Powder Technology Co., Ltd., with an average particle size of 30 nm; 9-decenal comes from Chongqing Zhengyuan Trading Co., Ltd.; calcium zinc composite stabilizer comes from Shandong Bangtai Petrochemical (Group) Co., Ltd.; chlorinated polyethylene (CPE) comes from Shandong Bangtai Petrochemical (Group) Co., Ltd., model: 135B; stearic acid comes from Dongguan Shanyi Plastic Chemical Co., Ltd., CAS No.: 57-11-4; chloroperoxybenzoic acid comes from Changzhou Zhuoxin Biotechnology Co., Ltd., CAS No.: 937-14-4; 4-amino-3-fluoroallyl benzoate comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 262433-55-6.

[0137] The high-performance and low-cost PVC cable protection tubes prepared in Examples 8-12 and the PVC composite cable protection tubes prepared in Comparative Examples 1-2 were tested for ring stiffness and room temperature impact performance according to the method described in GB / T 18477.1-2007 "Uniform polyvinyl chloride (PVC-U) structural wall pipe system for buried drainage Part 1: Double-wall corrugated pipes", wherein the impact performance is represented by the impact performance damage rate, wherein the impact performance damage rate (%) = total number of impact damages / total number of test impacts × 100%, repeated three times, and the average value was recorded. The specific test results are shown in Table 1;

[0138] Table 1

[0139]

[0140] As shown in Table 1, the high-performance, low-cost PVC cable protection tubes prepared in Examples 8-12 have good ring stiffness and impact resistance. The modified filler in Comparative Example 1 contains epoxy groups, which are beneficial to the stability of PVC. Once it is missing, the stability of the material is reduced, and its impact resistance is naturally reduced, so the impact resistance of Comparative Example 1 is lower than that of Example 1; Comparative Example 2 is compared with Comparative Example 1. In olefin-modified nano-calcium carbonate, 9-decenal is not introduced, and 9-decenal is a long-chain olefin aldehyde. The presence of its alkyl chain gives it a certain flexibility. Once it is missing, the impact resistance is reduced; and 4-amino-3-fluoroallyl benzoate itself can be used as a toughening agent. Once it is missing, its mechanical properties are naturally reduced, so the impact resistance of Comparative Example 3 is lower than that of Comparative Example 2.

[0141] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a high-performance and low-cost PVC composite material, characterized in that: The following steps are involved: PVC, modified filler, PNBR, impact resistant agent, heat stabilizer and lubricant are mixed evenly, heated, stirred, melted, extruded and granulated to obtain high-performance and low-cost PVC composite material; The preparation method of the modified filler comprises the following steps: Adding aldehyde-modified nano calcium carbonate-modified fly ash and 3-chloroperoxybenzoic acid into dichloromethane, reacting under low temperature conditions, filtering, washing, and drying after the reaction is completed, to obtain a modified filler; The preparation method of aldehyde-modified nano calcium carbonate-modified fly ash comprises the following steps: Step (1) in a nitrogen atmosphere, adding olefin-modified nano-calcium carbonate and 9-decenal to N,N-dimethylformamide, stirring, adding ammonium persulfate, heating, reacting, filtering, washing, and drying to obtain aldehyde-modified nano-calcium carbonate; Step (2) under an inert gas atmosphere, adding hydroxylated fly ash and 4-amino-3-fluoroallyl benzoate to N,N-dimethylformamide, adding potassium carbonate and mixing evenly, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain modified fly ash; Step (3) dispersing the aldehyde-modified nano-calcium carbonate into anhydrous ethanol, adding potassium hydroxide and modified fly ash after uniform dispersion, heating, reacting, filtering, washing, and drying to obtain aldehyde-modified nano-calcium carbonate-modified fly ash.

2. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The mass ratio of PVC, modified filler, PNBR, impact resistant agent, heat stabilizer and lubricant is (80-100):(12-18):(5-9):(8-16):(2-4):(1.4-1.8).

3. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The mass ratio of aldehyde-modified nano calcium carbonate-modified fly ash, 3-chloroperbenzoic acid and dichloromethane is (100-140):(400-600):(2000-4000); the reaction temperature is 1-5°C, and the reaction time is 2-4h.

4. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The mass ratio of olefin-modified nano-calcium carbonate, N,N-dimethylformamide, 9-decenal and ammonium persulfate is (60-80):(2000-4000):(30-50):(1.8-3); the reaction temperature is 65-75°C, and the reaction time is 2.5-4.5h.

5. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The mass ratio of hydroxylated fly ash, 4-amino-3-fluoroallyl benzoate, N,N-dimethylformamide and potassium carbonate is (70-90):(10-14):(800-1000):(2-4); the reaction temperature is 45-65°C, and the reaction time is 35-43h.

6. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The mass ratio of aldehyde-modified nano-calcium carbonate, anhydrous ethanol, potassium hydroxide and modified fly ash is (60-80):(1500-4500):(3-7):(20-28); the reaction temperature is 60-80°C, and the reaction time is 3-5h.

7. The method for preparing a high-performance and low-cost PVC composite material according to claim 1, characterized in that: The heat stabilizer is a calcium-zinc composite stabilizer.

8. A high-performance, low-cost PVC composite material prepared by the method for preparing a high-performance, low-cost PVC composite material according to any one of claims 1 to 7.

9. Use of the high-performance and low-cost PVC composite material according to claim 8 in a cable protection tube.

10. The use according to claim 9, characterized in that: The preparation of the cable protection tube using the high-performance and low-cost PVC composite material comprises the following steps: S1: Put PVC, modified filler, PNBR, impact agent, heat stabilizer and lubricant into a high-speed mixer, and mix them at high speed and low speed in sequence to obtain a mixture; S2: The mixed material is extruded through a twin-screw extruder, cooled, shaped, cut, and expanded to obtain a cable protection tube.

Citation Information

Patent Citations

  • Heat-resistant polyvinyl chloride cable protection tube and preparation method thereof

    CN112300515A

  • A high-strength PVC and preparation method thereof, and a cable protection tube

    CN118165434B

  • Environment-friendly high-performance PVC water supply pipe and preparation method thereof

    CN118085476A

  • High-strength PVC (polyvinyl chloride), preparation method and cable protection tube

    CN118165434A

  • Corrosion-resistant anti-icing coating and preparation method thereof

    CN118421143A